EFEKTIVITAS BAHAN ORGANIK SEBAGAI ATRAKTAN TERHADAP HAMA WALANG SANGIT (Leptocorisa sp.) PADA TANAMAN PADI - Sulistia Ningsih; Bunia Ceri (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2023)
Leptocorisa sp. is a pest of rice plants that can reduce crop yields by up to 50%. The use of chemical pesticides is still the main choice in controlling Leptocorisa sp. However, excessive use of pesticides can be bad for the environment and humans. This study aims to determine the type and height of attractant traps that are effective in controlling Leptocorisa sp. on rice plants. The study used a factorial Randomized Block Design (RBD) consisting of two factors. Observations were made for seven days with four repetitions. The distance between the traps is 5 meters. The results showed that Leptocorisa sp. males and females preferred golden snail traps compared to other types of material traps, namely 4.0 males and 2.5 females at a height of 0 cm, while at a height of 20 cm, there were 3.8 males and 3.3 females. This shows that Leptocorisa sp. males prefer golden snail traps to females. Leptocorisa sp. eggs. The highest was found in the pineapple skin bait treatment at a trap height of 40 cm with an average of 12.3 eggs, while the lowest was found in the golden snail bait treatment at a height of 20 cm with an average of 5.3 eggs. There are four insect families apart from Leptocorisa sp. those interested in traps include Calliphoridae, Muscidae, Blattellidae, and Formicidae.